Shifting the paradigm from pathogens to pathobiome: new concepts in the light of meta-omics - Vayssier-Taussat, Muriel; Albina, Emmanuel; Citti, Christine; Cosson, Jean François; Jacques, Marie-Agnès; LEBRUN, Marc-Henri; Le Loir, Yves; Ogliastro, Mylène; Petit, Marie-Agnès; Roumagnac, Philippe; Candresse, Thierry (Frontiers in Cellular and Infection Microbiology, 2014)
The concept of pathogenesis has evolved considerably over recent years, and the scenario “a microbe + virulence factors = disease” is probably far from reality in a number of cases. Actual pathogens have extremely broad biological diversity and are found in all major groups of microorganisms (viruses, bacteria, fungi, protozoa…). Their pathogenicity results from strong and often highly specific interactions they have with either their microbial environment, hosts and/or arthropod vectors. In this review, we explore the contribution of metagenomic approaches toward understanding pathogens within the context of microbial communities. With this broader view, we discussed the concept of “pathobiome” and the research questions that this raises.